2016
DOI: 10.1371/journal.pone.0160962
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity and Feasibility of Short Tests Currently Used to Measure Early Childhood Development in Large Scale Studies

Abstract: In low- and middle-income countries (LIMCs), measuring early childhood development (ECD) with standard tests in large scale surveys and evaluations of interventions is difficult and expensive. Multi-dimensional screeners and single-domain tests (‘short tests’) are frequently used as alternatives. However, their validity in these circumstances is unknown. We examined the feasibility, reliability, and concurrent validity of three multi-dimensional screeners (Ages and Stages Questionnaires (ASQ-3), Denver Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 34 publications
7
112
0
4
Order By: Relevance
“…The age group was determined to assess early child development which can be measured by using, Ages and Stages Questionnaire, with good accuracy [14]. Also, to catch children while they are still involved in early child development activities (breast feeding, consuming micronutrients, growth monitoring check-ups).…”
Section: Methodsmentioning
confidence: 99%
“…The age group was determined to assess early child development which can be measured by using, Ages and Stages Questionnaire, with good accuracy [14]. Also, to catch children while they are still involved in early child development activities (breast feeding, consuming micronutrients, growth monitoring check-ups).…”
Section: Methodsmentioning
confidence: 99%
“…The studies conducted by Rubio-Codina et al in Colombia did not find a correlation between performance in the ASQ-3 and the Bayley Scales of Infant and Toddler Development -American versionswithout considering population characteristics and local validations for any of the two scales. 25 A pilot study to compare the ASQ-3, the PRUNAPE, and the PRE-PRUNAPE screenings in Argentina showed that the ASQ-3 had the highest specificity and was more easily implemented. 26 Lastly, the frequency of neurodevelopmental disorders in the studied population was assessed, and it was consistent with the frequency of developmental delay reported for South American countries, with a higher incidence of deleterious socio-environmental factors (violence, inattention or neglect), growth deficit, and disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Los trabajos de Rubio-Codina y cols., no han encontrado, en Colombia, correlación entre el desempeño en el ASQ-3 con el test del desarrollo de Bayley usando versiones americanas, sin tener en cuenta las características de la población con validaciones locales para ninguna de las dos pruebas. 25 Un estudio piloto entre ASQ-3, PRUNAPE y PRUNAPE Prepesquisa en Argentina mostró la especificidad más alta para el ASQ-3 y mayor facilidad de implementación. 26 Por último, se evaluó la frecuencia de trastornos del neurodesarrollo en la población estudiada, que concordó con la frecuencia de retrasos en el desarrollo reportada para países sudamericanos, con mayor incidencia de factores deletéreos socioambientales (violencia, abandono o negligencia), déficit en el crecimiento físico y en el control de enfermedades.…”
Section: Tabla 2 Estadísticos Descriptivos Y Concordancia Entre El Cunclassified